Comparação entre implantes unitários de superfície tratada e não tratada por sub-tração radiográfica digital em protocolos de carga imediata e convencional - CARNEIRO, Luciano Sandoval (2009)
Objectives: To compare by digital subtraction radiography (SR), matched to clinical evaluation, bone response to single-tooth treated (TS) and non-treated (NTS) surface implants on immediate (IM) and conventional (CO) loading protocols. Material and methods: 12 patients (8 underwent IM protocol and 4 underwent CO protocol) received 24 implants. Each subject received 2 implants (one with TS and the other NTS) homologously and bilaterally positioned in maxillae (lateral incisor, canine or premolar regions) or mandible (molar area). Standardized radiographies of each implant were taken on the day after implant placement (baseline image) and after 3, 6 and 12 months (follow-up images). SR was used for crestal bone loss (CBL) and peri-implant bone density (PIBD) measurements. The placement torque and resonance frequency (at 0, 6 and 12 months) were also measured for matching radiographic data. Results: T-test revealed no statistically significant difference in CBL between TS and NTS implants, while TS implants presented higher PIBD in the mid-implant region at 3-months recall (p = 0.04). For IM protocol, the Mann-Whitney test revealed higher CBL at 6-months follow-up (p = 0.03), greater PIBD at 12-months recall (p = 0.06; p = 0.07) and increasing PIBD through time. There was a positive correlation between primary stability and PIBD at 12-months recall (r = 0.58; p = 0.005). Conclusions: TS and NTS implants presented similar performances with regard to CBL and PIBD. IM and CO protocols were similarly successful. Primary stability was an important element in reaching greater PIBD after 1-year loading period